Enhancing EFL Oral Proficiency Through Ice Breaking Activity: An Empirical Study of Motivation in Language Classroom - Buntara Adi Purwanto (Universitas Muhammadiyah Tangerang, 2026)
A classic problem in EFL speaking classes was students’ motivation for classroom engagement in speaking activities. To overcome the problem, the researcher proposed ice-breaking activities to reduce psychological boundaries. The aim of this research was to prove whether or not ice-breaking activities were able to improve students’ motivation, which directly influenced their speaking skill. This was empirical design research with a mixed method approach. The sample was taken by random sampling, which involved the first semester class of the English department program, containing of 23 students. The result was unpredictable since the improvement was not only occur in test score (10,38 points or 14,6%), but also questionnaire (4,18 points or 12,23%), and observation in phase 1 to phase 2 which showed students’ behavioural improvement from negative (Shy, silent, talking to friends, etc.) to positive (Speak louder, pay attention, asking question, etc.). This research led to the conclusion that ice-breaking activity could strengthened students’ motivation, improved oral fluency, and reduced affective obstacle.